Gamification in Project-Based Learning Using The Kahoot Application - Arifa, Rafikatul; Maulidi, Moh. Rizky; Kubro, Khodijatul; Hardiansyah, Framz (Journal of Practice Learning and Educational Development, 2026)
This research is motivated by the importance of innovation in learning methods to face educational challenges in the modern era. Project-based learning (PjBL) and gamification through the Kahoot application are alternatives for creating more interesting and meaningful learning. This research aims to identify the impact of gamification through Kahoot on the effectiveness of project-based learning and evaluate its effect on student motivation and learning outcomes. The method used is a systematic literature review by collecting data from various sources through searches on Google Scholar and Open Knowledge Maps using the keywords "Project Based Learning", "Gamification", and "Kahoot". From a total of 357,640 articles found, after going through two stages of screening based on specified criteria, 20 articles were obtained that were relevant for analysis. The research results show that the integration of gamification through Kahoot in PjBL can overcome various learning challenges such as difficulties in team collaboration and limited resources. The use of Kahoot has proven effective in increasing student motivation and active participation through its interactive features, even though there are technical limitations such as dependence on an internet connection. The implementation of a combination of these two methods succeeded in creating a more dynamic learning experience while maintaining the essence of meaningful learning